Inculcation of Emotional Intelligence in the English as a Second Language Classroom - Raja Abdul Aziz, Raja Mazuin (2004)
It is timely that in this millennium, the education fraternity be introduced to and progressively embrace a new concept called Emotional Intelligence (EQ). EQ has become another important element in measuring human intelligence and success. Therefore, it is crucial to make teachers aware of the importance of students becoming emotional literate. The purpose of this study was to explore and describe the inculcation of EQ in the ESL instruction in selected Smart School classrooms in Malaysia. The study was guided and carried out through the examination of four research questions: (1) How do the different ESL teachers’ EQ inform their practice as teachers?; (2) What is the extent of EQ being inculcated in the selected ESL classrooms in a Smart School by the different ESL teachers using Goleman’s viii checklist?; (3) How do elements associated with the inculcation of EQ in selected ESL classrooms in a Smart School affect the teaching of the different teachers?; and (4) What are the instructional strategies or activities used by the different teachers to inculcate EQ in the ESL Smart School classroom? The study employed qualitative methodology and the data were collected through interviews and classroom observations. Three ESL Smart School teachers were purposefully selected to participate in this study. The participants are trained secondary school teachers, teaching in a Smart School in the Federal Territory, Kuala Lumpur with at least two years of experience teaching ESL. They all teach in non- examination classes. The main sources of data were from the classroom observations that were video-taped and recorded which was later transcribed and analysed. Interviews were also carried out before and after observations to obtain their perceptions, experiences, and practices related to the study. The study revealed a number of findings. The findings are (1) elements like beliefs, time constraints, no training, lack of experience, personality, personal interest, syllabus, the education system, and fluency of the language impinge upon the participants’ use of EQ in the ESL classroom, (2) The Ministry of Education (MOE) whilst acknowledging the importance of EQ (Malaysia, 1997), needs to do more in inculcating EQ in schools, (3) participants in this study have different views about goals of education and appropriate means of achieving these goals. ix The study concludes that there is great disparity in understanding the concept of EQ as well as embracing it on equal footing against the established regime of IQ. The MOE has to show more commitment to break down years of mass acceptance of an old and perceived to be working concept. In order to effect change, a deeper understanding of EQ must be promulgated at the highest level namely MOE. If the following has been achieved, only then can EQ be implemented at the classroom level efficiently. Recommendations are proposed for further studies.